2-Deoxy-2-[fluorine-18] fluoro-d-glucose uptake on positron emission tomography is associated with programmed death ligand-1 expression in patients with pulmonary adenocarcinoma. (September 2018) - Kaira, Kyoichi; Shimizu, Kimihiro; Kitahara, Shinsuke; Yajima, Toshiki; Atsumi, Jun; Kosaka, Takayuki; Ohtaki, Yoichi; Higuchi, Tetsuya; Oyama, Tetsunari; Asao, Takayuki; Mogi, Akira
Abstract: 2-Deoxy-2-[fluorine-18] fluoro-d -glucose ( 18 F-FDG) positron emission tomography (PET) is a useful modality for the assessment of tumour glucose metabolism by upregulation by hypoxia. Little is known whether the uptake of 18 F-FDG within cancer cells is linked to the expression of programmed death ligand-1 (PD-L1), a predictor of anti–PD-1 antibody. We conducted a clinicopathological study to assess the expression of PD-L1 and tumour-infiltrating lymphocytes (TILs) in patients with surgically resected pulmonary adenocarcinoma (AC) who received preoperative 18 F-FDG PET. A total of 315 patients with lung AC who received 18 F-FDG PET were enrolled in the study. Tumour specimens were stained by immunohistochemistry for glucose transporter 1 (Glut1), hypoxia-inducible factor-1α (HIF-1α), PD-L1, CD4 and CD8. We assessed whether the uptake of 18 F-FDG was correlated with clinicopathological variables. PD-L1 was highly expressed in 60% of all patients with AC, and the expression level was significantly correlated with 18 F-FDG uptake, glucose metabolism and hypoxia. PD-L1 and the maximum standardised uptake value (SUVmax ) were identified as independent prognostic predictors by multivariate analysis. In particular, PD-L1 could be a significant marker for predicting worse outcomes in AC patients with high 18 F-FDG uptake but not in those with low 18 F-FDG uptake. According to the epidermal growth factor receptor ( EGFR ) mutation status, the expression of PD-L1 was significantly correlated with SUVmax in patients with EGFR mutation, whereas, PD-L1 was a significant predictive negative factor in those with wild-type EGFR . 18 F-FDG uptake was significantly correlated with PD-L1 expression, and the latter was closely linked to the presence of glucose metabolism and hypoxia in patients with pulmonary AC. Highlights: The accumulation of 2-Deoxy-2-[fluorine-18] fluoro-d -glucose is closely associated with the expression of programmed death ligand-1 (PD-L1) in lung adenocarcinoma. The PD-L1 expression significantly correlated with glucose metabolism and hypoxia. PD-L1 and maximum standardised uptake value were identified as independent prognostic predictors by multivariate analysis. PD-L1 was a significant prognostic predictor in patients with wild-type EGFR and high 18 F-FDG uptake.